Analisis Perkembangan Bahasa Pada Anak Usia 5-6 Tahun Di TK IT Almawaddah Semarang - Murgiyanti Murgiyanti; Sumarno Sumarno; Muhtarom Muhtarom (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
This research discusses the analysis of the development of language in children aged5-6years. The objectives of this study are (1) to determine the development of the language of children aged 5-6years; (2) to determine the factors of language development in children aged 5-6years. Understanding language is an initial effort to develop children‟s language development so that they can interact with their interlocutors. The type of research used is qualitative research with descriptive qualitative methods. Located in Islamic Kindergarten Almawaddah Semarang by looking at 2 research sources, namely 1 primary data source (educator) and secondary data source (3 early childhood children) aged5-6years. Data collection techniques used are interviews, observation and documentation. The data analysis techniques used are data reduction, data presentation, conclusion drawing and verification. The results of this study indicate that the analisysis of the development of language in children aged5-6years in Islamic Almawaddah Semarang develops as expected. The shortcoming in this study is the attachment which should be more complete with the results of the documenyation in the study and does not include the result of the video during observation and interviews at school. There are 4 indicators of language development of children aged5-6years, namely: a). Understand multiple commands at the same time. b). repeating more complex sentences. c). Understand the rules of a game. d). Enjoy and appreciate reading. The implication of the research shos that early childhood aged 5-6 years are expected to keep the spirit of learning independently at home to be able to further develop the development of understanding language in children, educators and parent are expected to pay more attention in providing lessons for their children so that their ability to understand children‟s language can develop. And researchers are expected to be more creative in conducting future research and further researchers, in order to obtain maximum results.